How to Improve Israel's Health-care System - Hemmings, Philip (OECD Publishing, 2014)
Israelis enjoy higher life expectancy and have a much younger demographic profile than most OECD countries. However, the demand for health care is expanding rapidly due to population growth and ageing. Also, the country's wide socio-economic divides are reflected in differences in health outcomes. To date the health-care system, centred on four health funds, is widely acknowledged as providing a basket of universal services, with good quality primary and secondary care, while also accommodating demand for private health care. However, there are challenges and tensions in the system. Currently the authorities are having to rapidly expand the number of places in medical schools and nurse training because large cohorts of health-care professionals are heading for retirement. More broadly, there are concerns that the core notion of a universal basket of services is being eroded by co-payments and the increasing demand for the additional services and options provided by private insurance. Although the quality of care is generally good, in hospital care there is room to improve data and concern that overcrowding may become chronic. This Working Paper relates to the 2013 OECD Economic Review of Israel (www.oecd.org/eco/surveys/economicsurvey- israel.htm)
Keywords: Social Issues/Migration/Health; Economics; Israel